2013
DOI: 10.3171/2013.6.peds13112
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of academic productivity in pediatric neurosurgery

Abstract: Object Various bibliometric indices are now commonly used to assess academic productivity in medicine. Some evidence suggests that these measures are specific to subspecialty areas. The authors' goal was to measure the h index of academic pediatric neurosurgeons and compare it with previously reported results for academic neurosurgeons in general. Methods Programs with an Accre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…General, spine, and pediatric neurosurgeons had lower bibliometrics compared with peripheral nerve, neuro-oncology/skull base, radiosurgery, functional/epilepsy, and vascular neurosurgeons. With the exception of the recent paper by Kalra and Kestle, 29 this represents the first attempt to compare publication productivity among neurosurgical subspecialties. Kalra and Kestle used Google Scholar (Harzing's Publish or Perish) to determine the h-and g-indices for 72 academic pediatric neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…General, spine, and pediatric neurosurgeons had lower bibliometrics compared with peripheral nerve, neuro-oncology/skull base, radiosurgery, functional/epilepsy, and vascular neurosurgeons. With the exception of the recent paper by Kalra and Kestle, 29 this represents the first attempt to compare publication productivity among neurosurgical subspecialties. Kalra and Kestle used Google Scholar (Harzing's Publish or Perish) to determine the h-and g-indices for 72 academic pediatric neurosurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,12,[14][15][16]24,27,31,32 In 2013, Kalra and Kestle that host accredited pediatric fellowship programs. They found that the publishing productivity of the pediatric neurosurgeons in these groups, measured using the h-and g-indices, was on par with the productivity of neurosurgeons in all academic departments.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…We chose the second methodology to adequately include those journals that, although unconventional, may contain high-impact articles. The publication history of the top 25 North American pediatric neurosurgeons was chosen based on the h-index because the h-index is a measure of career productivity, and as such, these clinicians have a proven track record of highimpact articles [17,20]. A 5-year publication history of the top 25 neurosurgeons was chosen to provide an adequate and current sample of references from which to draw meaningful conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These bibliometric indices-the h-index in particular-have been widely applied to neurosurgery [17][18][19][20][21][22][23][24][25]. Using this database, we identified the 25 top-ranked North American pediatric neurosurgeons based on the manually calculated h-index from Scopus (Elsevier, www.scopus.com) [17].…”
Section: Introductionmentioning
confidence: 99%